Unusually Rapid Response In Psoriasis Treated With PUVA. - Joshi Rajiv S; Chavan Rajashree; Phadke Vaishali A; Khopkar Uday S; Wadhwa Satish L (Wolters Kluwer Medknow Publications, 1999)
Two cases of psoriasis under PUVA therapy presented for its unusual rapid response with quick clearance of lesions within three weeks.